2012
DOI: 10.1186/gm300
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipids and insulin resistance in psychosis: a lipidomics study of twin pairs discordant for schizophrenia

Abstract: BackgroundSeveral theories have been proposed to conceptualize the pathological processes inherent to schizophrenia. The 'prostaglandin deficiency' hypothesis postulates that defective enzyme systems converting essential fatty acids to prostaglandins lead to diminished levels of prostaglandins, which in turn affect synaptic transmission.MethodsHere we sought to determine the lipidomic profiles associated with schizophrenia in twin pairs discordant for schizophrenia as well as unaffected twin pairs. The study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 45 publications
2
73
1
1
Order By: Relevance
“…Partial correlations were calculated between the O-PLS-DA identified top 10% feature set and all statistically significant T1D-associated perturbations. This was achieved using reduced order or q-order partial correlations (Castelo and Roverato 2009) (q=1, 19, 38, 56, n=1000), which have been previously implemented for Gaussian graphical models of high-dimensional metabolomic data (Oresic et al 2012). An average non-rejection rate β=0.4 was used as a criteria for accepting pairwise relationships, for which coefficients of partial correlation, p-values and FDR adjusted p-values(Benjamini Y 1995) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Partial correlations were calculated between the O-PLS-DA identified top 10% feature set and all statistically significant T1D-associated perturbations. This was achieved using reduced order or q-order partial correlations (Castelo and Roverato 2009) (q=1, 19, 38, 56, n=1000), which have been previously implemented for Gaussian graphical models of high-dimensional metabolomic data (Oresic et al 2012). An average non-rejection rate β=0.4 was used as a criteria for accepting pairwise relationships, for which coefficients of partial correlation, p-values and FDR adjusted p-values(Benjamini Y 1995) were calculated.…”
Section: Methodsmentioning
confidence: 99%
“…It has been noted in particular that there is an increase in stochastic methylation variability in regions which are already known to have altered levels of methylation in cancers, leading to aberrant and varying gene expression, and providing an epigenetic mechanism for tumour heterogeneity [8]. It has also been shown recently that statistics based on differential variability of methylation can lead to improved detection of risk markers in pre-cancerous growths [9], [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [7], [9], [10] have focussed on the effects of sample to sample variability of methylation; here for the first time, we analyse the association of phenotype with intra-gene variability of methylation. Making use of data derived from the Illumina Infinium HumanMethylation450 platform, which interrogates CpGs genome-wide including with known gene annotations (corresponding to on average 17 CpGs per gene), we have investigated measures of intra-gene methylation architecture, and their ability to differentiate between healthy and disease phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…A study of twins, with one of the twins being schizophrenic, showed that the schizophrenic twin had elevated levels of ether lipids (such as phosphatidylethanolamines and phosphatidylcholines), abundant triglycerides as well as long-chain and PUFA (polyunsaturated fatty acids)-containing triglycerides [46]. However, their healthy twins had higher concentrations of PUFA-containing phosphatidylcholines and phosphatidylethanolamines, lysophosphatidylcholines and short-chain saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA)-containing triglycerides.…”
Section: Neuropsychiatric Disorders Schizophreniamentioning
confidence: 99%